Kombinasi Latihan Isometrik & Isotonik Pada Otot Quadriseps Dapat Mengurangi Nyeri Lutut Pada Pasien OA Knee Bilateral di RSUD Ibnu Sina Kabupaten Gresik - Palupi, Retno Isti; Fariz, Achmad; Prisusanti, Retno Dewi; Endaryanto, Agung Hadi (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:  Bilateral knee OA is a degenerative disease that occurs on both sides of the knee joint due to the wear and tear of the articular cartilage and the formation of new bone on the joint surface which can cause muscle and tendon weakness, limit movement and cause pain. One of the pain reduction measures in bilateral knee OA patients can be maximized by giving a combination of isometric and isotonic quadriceps exercises. Repeated movements in the quadriceps muscle will increase the work of the muscles around the knee joint so that blood flow will increase which will increase metabolism and stimulate the release of endorphins which can reduce the sensation of pain and stiffness of the knee joint. The combination of isometric and isotonic exercises on the quadriceps muscle can increase the strength of the quadriceps, thereby increasing blood flow which will increase the body's metabolism, make the knee joint more stable, and make the knee joint more stable.Methods:   This type of research is a quasi-experimental non-equivalent group design method (pre-test and post-test). The sample in this study were 20 respondents who suffered from bilateral knee OA who were in Ibnu Sina Hospital, Gresik Regency. Respondents were given a combination of isometric and isotonic quadriceps exercise twice a week for four weeks. Pre and post tests were carried out on respondents to determine the reduction in knee pain scale. Data analysis used the Wilcoxon Signed Rank Test and the Saphiro Wilk Test at a significance level of p-value < 0,05.Results:  Normality test with Shapiro Wilk test data obtained before and after the test treatment group data is not normally distributed. Test the effect on the treatment before and after the treatment group test by giving a combination of isometric and isotonic exercises on the quadriceps muscle using the Wilcoxon sign rank test,there is a significant value for the right knee, namely the p value (0.001 < 0.05) and the left knee, namely the p value (0.004 < 0.05) this means that H0 is rejected, it can be concluded that there is an effect of a combination of isometric and isotonic exercises on the quadriceps muscle to reduce knee pain in bilateral knee OA patients.Conclusion:  The results of this study indicate that the combination of isometric and isotonic exercises on the quadriceps muscle is proven to significantly reduce knee pain in patients with bilateral knee OA.